Visuospatial Ability as a Predictor of Novice Performance in Ultrasound-Guided Regional Anesthesia. Issue 3 (June 2016) - Shafqat, Atif; Ferguson, Eamonn; Thanawala, Vishal; Bedforth, Nigel M.; Hardman, Jonathan G.; McCahon, Robert A.
Abstract : (Abstracted from Anesthesiology, 123:1188–1197, 2015) Ultrasound-guided regional anesthesia (USGRA) requires manual dexterity and hand-eye coordination and is related to an individual's ability to mentally rotate and manipulate 2- and 3-dimensional objects (visuospatial testing). The primary goal of this study was to determine whether visuospatial ability could predict technical performance of an ultrasound-guided needle task by novice operators.